Integrated Marketing Communication, STP, and SWOT Strategies in Enhancing Garudafood's Competitiveness - Alan Handiananto (Journal of Business, Social and Technology, 2026)
Background: The food and beverage industry in Indonesia is growing; however, competition among companies remains intense due to rapidly evolving consumer preferences. Therefore, supply cannot be continuously increased without adaptive marketing strategies. To become more competitive in the national FMCG market, PT Garudafood Putra Putri Jaya Tbk requires integrated strategic approaches. Objective: This empirical study focuses on the Integrated Marketing Communication (IMC), Segmentation, Targeting, and Positioning (STP), and Strengths, Weaknesses, Opportunities, and Threats (SWOT) factors influencing Garudafood’s competitiveness. Methods: This study involves a literature review and company document analysis using a qualitative descriptive approach. The data were analyzed using content analysis, focusing on IMC implementation, STP strategies, SWOT factors, product innovation, distribution strategies, consumer responses, and digital marketing practices. Results: The results reveal that Garudafood’s competitiveness is based on strong brand awareness, extensive market segmentation, value-for-money positioning, wide distribution networks, and accessibility that enable the company to reach consumers in all areas through both digital marketing and integrated promotional activities. However, despite having contingency plans, limited product innovation remains a strategic weakness that needs to be addressed. Conclusion: Integrating IMC, STP, and SWOT strategies contributes to strengthening Garudafood’s market position and competitiveness. In Indonesia’s food and beverage industry, continuous innovation, digital engagement, and proactive strategic management are paramount to maintaining a competitive edge.